Entre a letra e o espírito: o discurso de professores(as) sobre estudantes negros (as) pós-implementação da Lei 10.639/03 em escola pública - Andrade, Alcilene da Costa (2011)
This study proposes to analyze the discourse of teachers about black students after the implementation of the Federal Law 10.639/2003, which made obligatory the teaching of African history and culture in formal education. In a specific way, we intend to identify the teacher s discourse about black students after this law, as well as the effects of sense produced by the teacher s discourse about black students and comprehend the teacher s discourse after this law, in order to understand the effects of sense produced by this law in the teacher s practice. Is assumed that this law, like all discourse, comes from many statements coming from the same discursive formation , formed in different socio-historical contexts, controlling what should be said or not in a given space-time. We made use of the epistemology of Cultural Studies that, as a field of knowledge, deal with issues related to identity and difference and has as main point for its studies the relationship between contemporary culture and society, and from a social point of view, make possible to analyze meanings and the values implicit and explicit in a way of life. Using a qualitative approach, we had as a basis the tenets of Discourse Analysis, trying to highlight the voices of 05 teachers from three schools of João Pessoa by means of semi-structured interviews, in order to understand the effects of meaning in their teaching practice. The research corpus is composed by law, DCNs (national curriculum guidelines) of Racial and Ethnic Relations Education, National Plan for Implementation of the these DCNs and the political pedagogical project of one public school. The research results leads us to recognize the urgent need to monitor the implementation of Law 10.639/03 through a teacher training which enables a regard of teachers on black students able to promote changes in the filed of education of racial and ethnic relations.